Permeation of Na+ through a delayed rectifier K+ channel in chick dorsal root ganglion neurons (The Rockefeller University Press, 1994)
In whole-cell patch clamp recordings from chick dorsal root ganglion neurons, removal of intracellular K+ resulted in the appearance of a large, voltage-dependent inward tail current (Icat). Icat was not Ca2+ dependent and was not blocked by Cd2+, but was blocked by Ba2+. The reversal potential for Icat shifted with the Nernst potential for [Na+]. The channel responsible for Icat had a cation permeability sequence of Na+ >> Li+ >> TMA+ > NMG+ (PX/PNa = 1:0.33:0.1:0) and was impermeable to Cl-. Addition of high intracellular concentrations of K+, Cs+, or Rb+ prevented the occurrence of Icat. Inhibition of Icat by intracellular K+ was voltage dependent, with an IC50 that ranged from 3.0-8.9 mM at membrane potentials between -50 and -110 mV. This voltage- dependent shift in IC50 (e-fold per 52 mV) is consistent with a single cation binding site approximately 50% of the distance into the membrane field. Icat displayed anomolous mole fraction behavior with respect to Na+ and K+; Icat was inhibited by 5 mM extracellular K+ in the presence of 160 mM Na+ and potentiated by equimolar substitution of 80 mM K+ for Na+. The percent inhibition produced by both extracellular and intracellular K+ at 5 mM was identical. Reversal potential measurements revealed that K+ was 65-105 times more permeant than Na+ through the Icat channel. Icat exhibited the same voltage and time dependence of inactivation, the same voltage dependence of activation, and the same macroscopic conductance as the delayed rectifier K+ current in these neurons. We conclude that Icat is a Na+ current that passes through a delayed rectifier K+ channel when intracellular K+ is reduced to below 30 mM. At intracellular K+ concentrations between 1 and 30 mM, PK/PNa remained constant while the conductance at -50 mV varied from 80 to 0% of maximum. These data suggest that the high selectivity of these channels for K+ over Na+ is due to the inability of Na+ to compete with K+ for an intracellular binding site, rather than a barrier that excludes Na+ from entry into the channel or a barrier such as a selectivity filter that prevents Na+ ions from passing through the channel.